The Effect of COCO Movie Towards Students’ Writing of Narrative Texts - Sumiatik Sumiatik; Muhamad Sofian Hadi; Hasanul Misbah (Universitas Cokroaminoto Palopo, 2021)
The research aims to prove COCO Movie is effective in teaching writing of narrative texts. This research conducted in SMP Al-Madinah Islamic Center KKMB Tangerang Selatan. The population of this research is eight grade students, and the sample of research was 29 students of 8th class. The method of this research is quantitative method and using pre – experimental design. To collect the data, the researcher used pre – test and post – test that to given the students. The result score of the data indicated that, the total of score of students in pre – test were 1.917 with the mean score was 66.10. The lowest 45 and the highest score were 85. The total score of students in post – test were 2.343 with the mean were 78.38. the lowest score 65 and the highest score were 95. The researcher conducted pre – test and post – test to collect the data and used paired t-test to analyze the data through SPSS 24. The t-value of test was 10.176 and t-value of DF was 2.048. Because the t-value of test was higher than t-value of df (10.176>2.018). The reseacher was succesful and COCOMovie was effective to improve student’s writing skill for narrative text in class Eighth at SMP Al-Madinah Islamic Center KKMB Tangerang Selatan.